Biotechnological promises of Fe-filled CNTs for cell shepherding and magnetic fluid hyperthermia applications. Issue 48 (19th November 2015) - Pineux, Florent; Marega, Riccardo; Stopin, Antoine; La Torre, Alessandro; Garcia, Yann; Devlin, Eamonn; Michiels, Carine; N. Khlobystov, Andrei; Bonifazi, Davide
Abstract : Chemical modulation of the iron loading and crystallinity in Fe-filled carbon nanotubes yield derivatives with promising cell shepherding and magnetic fluid hyperthermia performances. Abstract : Fe-filled carbon nanotubes (Fe@CNTs) recently emerged as an effective class of hybrid nanoparticles for biotechnological applications, such as magnetic cell sorting and magnetic fluid hyperthermia. Aiming at studying the effects of both the Fe loading and the magnetocrystalline characteristics in these applications, we describe herein the preparation of Fe@CNTs containing different Fe phases that, upon functionalization with the antibody Cetuximab (Ctxb), allow the targeting of cancer cells. Our experimental findings reveal that an optimal Ctxb/Fe weight ratio of 1.2 is needed for efficient magnetic cell shepherding, whereas enhanced MFH-induced mortality (70 vs. 15%) can be reached with hybrids enriched in the coercive Fe3 C phase. These results suggest that a synergistic effect between the Ab loading and the Fe distribution in each nanotube exists, for which the maximum shepherding and hyperthermia effects are observed when higher densities of Fe@CNTs featuring the more coercive phase are interfaced with the cells.